Publishing in Small Business Economics: An Entrepreneurship Journal - David B. Audretsch; Christina Guenther; Adam Lederer (Small Business Economics, 2021)
Plain English Summary Publishing entrepreneurship research is not just important but challenging. Longstanding experts in the field can provide helpful advice. As borders between academic fields blur, research fields are increasingly global in their perspective, knowledge, and findings, thus enabling robust participation in research fields at a scale previously unimaginable. Drawing on the experience, insights, and perspectives of three seasoned editors, we try to reconcile the seemingly incoherent and inherent frustration experienced by researchers, on the one hand, with the very purposeful and self-aware process of at least one scholarly journal, Small Business Economics: An Entrepreneurship Journal, on the other, to provide guidelines and insights to aspiring authors in what they should consider in crafting their research for submission with the goal of publication. In providing this sage council, the paper provides guidance to researchers on the process of publishing their results.
Keywords: 330; L26; M1; M2; M13; M20; M2